Experimental Evaluation of the effect of Fan Pad Evaporative Cooling System parameters on Greenhouse Cooling - Yadav, Vinod Kumar; Singh, Amar; Chandra, P (Journal of Agricultural Engineering, 2002)
Experiments were conducted to evaluate the effect of fan-pad evaporative cooling system parameters on greenhouse cooling. The fan-pad cooling system parameters were thickness of the pad (50,75 and 100 mm), airflow rate (0.3, 0.45, 0.6 and 0.75 m/s) and water flow rate (5, 10 and 15 1/min). The dependent parameters were cooling efficiency, pressure drop and energy consumption. The results showed that if air and water flow rates were not limiting, pad-thickness did not have any effect on green house cooling. The pressure drop increased with increase in airflow rate and pad-thickness. The energy consumption did not vary significantly as a function of system parameter.